Bettina Arndt interviewed by Sara Dowse - Arndt, Bettina, 1949-; Dowse, Sara, 1938- (2007)
Bettina Arndt speaks about her parents; her family background; migrating to Australia; life in Canberra in the 1950's; her childhood memories; her schooling; Canberra University; 'Forum' magazine; Clyde Packer; media appearances; her love of radio; Dennis Minogue; her marriage and death of husband; running 'Forum'; responses to magazine; visiting America; widowhood; broadening content of magazine; closing 'Forum'; media career; meeting second husband; adjusting to New York (1986); her two children; returning to Australia (1991); the revamping of child support scheme; state contribution to child support; Party political issues; Child care; original child care policy; issues about children and divorce; post-separation for children; increasing marital breakdown; women's expectations of men in relationships; state of transition since women's revolution; marital conflict; changing human nature; Feminism; general fear in society; relationships and children; comparing boys with girls; importance of steadiness in relationships for children; greatest satisfaction in life; women friends; men's 'unexamined lives'; how to organise society for better balance for individuals.
Recorded on January 19, 2007 at Bronte, N.S.W.
Digital master available
Bettina Arndt born 1949 in Penrith, U.K., a well-known social commentator who began her career in the 1970's as one of Australia's early sex therapists, and was editor to the Australian edition of 'Forum'. In 1981 Arndt began full-time feature writing, was a regular newspaper columnist and made frequent appearances in the broadcast media. In 1991 she became involved through her writings and participation on relevant government bodies in reforming family policy. Arndt is the author of three books Private Lives (1986), All About Us (1989), Taking Sides (1995). In 2000-2001 she was president of the foundation of Sydney's Royal Hospital for Women.
Timed summary and uncorrected transcript (typescript, 73 leaves) available.
Keywords: Arndt, Bettina, -- 1949- -- Interviews; Authors, Australian -- Interviews; Journalists -- Australia -- Interviews; Family policy -- Australia